H\(_2\) adsorption isotherms of Mg-MOF-74 isoreticulars: An integrated approach utilizing a thermochemical model and density functional theory - Nguyen, Thuy-Trang; Cong-Phuong, Cao; Le-Hoang, Phong; Nguyen-Hoang, Linh; Vu-Hoang, Nam; Nguyen The, Toan; Phan Bach, Thang (Communications in Physics, 2023)
A thermochemical model was developed to calculate the H2 adsorption isotherm of the original Mg-MOF-74 framework, and its computationally designed isoreticular employing the adsorption energies and vibrational frequencies obtained from density functional theory calculations as input variables. The model reasonably replicates the experimental adsorption isotherm of the original framework at -196oC within the pressure range up to 1 bar. The strongest adsorption site of the new Mg-MOF-74 isoreticular exhibits saturation at lower pressure compared to the original one, despite a lower adsorption energy. This emphasizes the importance of vibrational, rotational, and translational contributions for comprehensively assessing the site’s adsorption performance. Because only the strongest adsorption site was taken into account for the site-site interaction, the model is only valid for low coverage rates of secondary sites. Consequently, it strongly overestimates the hydrogen uptake of the original isoreticular at higher temperature and pressure ranges where the cumulative coverage rate of the secondary adsorption sites is comparable to that of the strongest sites. In contrast, the model remains valid for the new isoreticular at a specific temperature between -40oC and 60oC within the pressure range up to 25 bar where the coverage rate of the secondary adsorption site is low. Its predictions highlights the significantly improved performance of the new framework compared to the original framework. Specially, it achieves a gravimetric hydrogen uptake value between 2.8 wt% and 1.9 wt% at a pressure of 25 bar within the mentioned temperature swing which is substantially higher than that of the original framework.